Discovery of reversing enzymes for RNA ADP-ribosylation reveals a possible defence module against toxic attack - Lu, Y; Schuller, M; Bullen, N; Mikolcevic, P; Zonjic, I; Raggiaschi, R; Mikoc, A; Whitney, J; Ahel, I (Oxford University Press, 2025)
Nucleic acid ADP-ribosylation and its associated enzymes involved in catalysis and hydrolysis are widespread among all kingdoms of life. Yet, its roles in mammalian and bacterial physiology including inter-/intraspecies conflicts are currently underexplored. Recently, several examples of enzymatic systems for RNA ADP-ribosylation have been identified, showing that all major types of RNA species, including messenger RNA, ribosomal RNA, and transfer RNA, can be targeted by ADP-ribosyltransferases (ARTs) which attach ADP-ribose modifications either to nucleobases, the backbone ribose, or phosphate ends. Yet little is known about the reversibility of RNA ADP-ribosylation by ADP-ribosylhydrolases belonging to the macrodomain, ARH, or NADAR superfamilies. Here, we characterize the hydrolytic activity of ADP-ribosylhydrolases on RNA species ADP-ribosylated by mammalian and bacterial ARTs. We demonstrate that NADAR ADP-ribosylhydrolases are the only hydrolase family able to reverse guanosine RNA base ADP-ribosylation while they are inactive on phosphate-end RNA ADP-ribosylation. Furthermore, we reveal that macrodomain-containing PARG enzymes are the only hydrolase type with the ability for specific and efficient reversal of 2′-hydroxyl group RNA ADP-ribosylation catalysed by Pseudomonas aeruginosa effector toxin RhsP2. Moreover, using the RhsP2/bacterial PARG system as an example, we demonstrate that PARG enzymes can act as protective immunity enzymes against antibacterial RNA-targeting ART toxins.